Antibiotics are not necessary during routine cystoscopic stent removal: A randomized controlled trial at UC San Diego - Bradshaw, Aaron; Pe, Mark; Bechis, Seth; Dipina, Thomas; Zupkas, Paul; Abbott, Joel; Papagiannopoulos, Dimitri; Cobb, Kaitlan; Sur, Roger (Urology annals, 2020)
Introduction: Current American Urological Association (AUA) Best Practice Statement recommends antibiotic prophylaxis for cystoscopy with manipulation, including stent removal; although no Level 1b trials explicitly address prophylaxis for stent removal. We sought to determine the efficacy of prophylactic antibiotics to prevent infectious complications after stent removal. Materials and Methods: Following institutional review board approval, patients undergoing removal of ureteral stent placed during stone surgery were recruited from July 2016 to March 2019. Patients were recruited at the time of stent removal and randomized to treatment (single dose 500 mg oral ciprofloxacin) or control group (no antibiotics). Telephone contact was attempted within 14 days of stent removal to assess for urinary tract infection (UTI) symptoms, antibiotic prescriptions, or Emergency Department visits. Primary outcome was UTI within 1 month of stent removal - defined by irritative voiding symptoms, fever or abdominal pain associated with positive urine culture (Ucx) (>100k colony-forming units/mL). Results: Seventy-seven patients were enrolled, with 58 meeting final inclusion criteria for the analysis (33 treatment, 25 controls). No differences were seen with clinical and demographic variables, except a higher body mass index in the treatment group (P = 0.007). Positive Ucx rate before stone surgery (16.7% vs. 11.8%, P = 0.819) and at the time of stent removal (16.0% vs. 11.1%, P = 0.648) was not significantly different in treatment versus control groups, respectively. Primary outcome: No patients in either cohort developed symptomatic culture-diagnosed UTI within 1 month of stent removal. Of patients with documented phone follow-up (treatment n = 29, control n = 22), only one patient (control) reported any positive response on phone survey. Conclusions: We found a low infectious complication rate regardless of antibiotic prophylaxis use during cystoscopic stent removal. The necessity of antibiotics during routine cystoscopic stent removal warrants possible reevaluation of the AUA best practice statement.